Librarian as Innovator: Redesigning Library Services through Participatory Co-Creation Models - Sulham, Baso; Reza, Ali; Rahimi, Ramin (Yayasan Adra Karima Hubbi, 2025)
Libraries are increasingly recognized as dynamic knowledge hubs that must adapt to rapidly changing user expectations and technological advancements. The traditional service-oriented model of librarianship is no longer sufficient to address the complex and evolving needs of diverse user communities. This study aims to explore how librarians function as innovators by implementing participatory co-creation models to redesign library services. A mixed-method research approach was employed, combining a systematic review of 68 empirical studies with multiple case studies from academic and public libraries. Data were collected through document analysis, interviews, and focus group discussions, and were analyzed using thematic coding and cross-case synthesis. Findings reveal that participatory co-creation models foster a culture of innovation, enabling libraries to develop services that are user-centered, technologically integrated, and socially inclusive. The evidence demonstrates that collaborative approaches increase community engagement, enhance digital literacy programs, and expand the relevance of library services in the digital era. This study concludes that librarians, when positioned as co-creators and facilitators of innovation, can transform libraries into participatory spaces that respond effectively to local and global challenges. Recommendations highlight the need to institutionalize co-creation practices as a strategic framework for sustainable library development.